Trade, Aid and Terror - Simplice A. Asongu; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2015)
This study assesses the role of foreign aid in reducing the hypothetically negative impact of terrorism on trade using a panel of 78 developing countries with data for the period 1984-2008. The empirical evidence is based on interactive GMM estimations with forward orthogonal deviations. Bilateral, multilateral and total aid dynamics are employed whereas terrorism entails: domestic, transnational, unclear and total terrorism dynamics. The following findings have been established. First, while bilateral aid has no significant effect on trade, multilateral and total aids have positive impacts. Second total terrorism, domestic terrorism and transnational terrorism increase trade with increasing order of magnitude. Third, corresponding negative marginal effects on the interaction between foreign aid (bilateral and total) and terrorism display thresholds that are within range. Unexpected signs are clarified and policy implications discussed.
Keywords: F40; F23; F35; O40; 330; Trade Openness; Foreign Aid; Terrorism; Development